Implementasi Akad Murabahah Pada Produk Pembiayaan BMT As’sadiyah Sengkang: Studi Syariah dan Ekonomi - Nurhidayah Nurhidayah; Rosmini Rosmini; A.Wulandari; Sitti Nikmah Marzuki (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Baitul Maal Wat Tamwil (BMT) is a sharia-based microfinance institution that plays a role in providing financing to the community, particularly micro-entrepreneurs, to help them avoid reliance on loan sharks. This study focuses on the implementation of the murabahah contract at BMT As'adiyah Sengkang, using a descriptive qualitative approach through interviews, observations, and document analysis. The findings indicate that the murabahah contract is implemented based on the principles of Islamic justice, involving transparency in pricing and profit margins while ensuring that transactions are conducted voluntarily. The financing mechanism includes customer eligibility surveys, financial capacity analysis, and the determination of fair profit margins. This murabahah contract significantly benefits the local economy by facilitating access to interest-free financing without late payment penalties. In conclusion, the implementation of the murabahah contract at BMT As'adiyah Sengkang aligns with sharia values, supports the economic empowerment of the Muslim community, and contributes to the growth of sharia-based financial inclusion at the local level.